2016
DOI: 10.1039/c6cp02029a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of thermal properties of borophene

Abstract: Very recently, a new single-element two-dimensional (2D) material borophene was successfully grown on a silver surface under pristine ultrahigh vacuum conditions which attracts tremendous interest. In this paper, the lattice thermal conductivity, phonon lifetimes, thermal expansion and temperature dependent elastic moduli of borophene are systematically studied by using first-principles. Our simulations show that borophene possesses unique thermal properties. Strong phonon-phonon scattering is found in borophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
97
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 46 publications
(60 reference statements)
16
97
1
Order By: Relevance
“…19 The monolayer borophene with rectangular structure attracts lots of interest due to its extraordinary properties. [19][20][21][22][23] Borophene possesses extraordinary mechanical property of extremely large Young's modulus which may rival that of graphene. 19,22 It is also revealed that borophene is a highly anisotropic 2D metal, 19 making its electronic and magnetic properties can be orientation controlled.…”
Section: Introductionmentioning
confidence: 99%
“…19 The monolayer borophene with rectangular structure attracts lots of interest due to its extraordinary properties. [19][20][21][22][23] Borophene possesses extraordinary mechanical property of extremely large Young's modulus which may rival that of graphene. 19,22 It is also revealed that borophene is a highly anisotropic 2D metal, 19 making its electronic and magnetic properties can be orientation controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The superconducting transition temperature T c of borophene is about 19 K, which can be increased to 27.4 K by applying a tensile strain, or 34.8 K by hole doping 9 . Due to the strong phonon-phonon scattering, the lattice thermal conductivity of borophene is unexpectedly low 20 . Recently, Feng et al synthesized two boron sheets: Ī² 12 and Ļ‡ 3 , both of which belong to the triangular lattice but differ in arrangements of periodic holes 21 .…”
Section: Introductionmentioning
confidence: 99%
“…36 Undoubtedly, the experimental realization of borophene raises the hope that it might serve as a high-speed pathway for phonon transport, due to its short covalent bonds and light atomic mass. Although the thermal conductivity 37,38 and thermal conductance 39 of borophene have been explored, the ballistic phonon transport mechanisms and properties of borophene are still largely unknown, and thus a solid understanding is needed in order to provide guidance for the exploration of its applications.…”
Section: Introductionmentioning
confidence: 99%